The Effect of Learning Strategy of Everyone Is a Teacher Here on The Learning Outcomes of Islamic Religious Education - Indrayati Indrayati; Edwin Hadiyan; Safrawali Safrawali; Alifvia Indah Safitri; Muhammad Husnur Rofiq (STAI Hubbulwathan Duri, 2022)
The purpose of this research is to find out how the influence of learning outcomes on students in Islamic Education subject using the Everyone Is a Teacher Here strategy at SMPN 1 Gondang. This research was carried out from January to February 2022. The approach used in this research is a quantitative approach with a Group Pre-Test and Post-Test Design. The instrument used for the test is multiple-choice questions that have gone through the validity test process. The sample of this study was grade 7 SMPN 1 Gondang which amounted to 58 students. The results of the study indicate that there is an influence on the use of the Everyone Is A Teacher Here strategy on student learning outcomes in Islamic Education subjects. The result can be proven by increasing the average value of student learning outcomes from 72.41 to 76.47 and can be known through hypothesis testing by using the t-test to obtain the value of Sig. (2-tailed) 0,016 ≤ 0,05 and get the value of t-test t-count ≥ t-table 2,473 ≥ 1,672it means Ha is accepted and H0 is rejected. From the research that has been done, it can be concluded that the learning strategy Everyone Is A Teacher Here affects the learning outcomes of students in Islamic Education.